2017
DOI: 10.3906/biy-1604-80
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and enhanced antimicrobial activity: quercetin-loaded PLGA nanoparticles against foodborne pathogens

Abstract: The use of quercetin as a bioflavonoid is becoming increasingly common in food industries even though poor water solubility, instability, absorption, and permeability have limited its application. The oil-in-water single-emulsion solvent evaporation method to synthesize highly stable and soluble quercetin-encapsulated nanoparticles (NPs), in which the reaction yield, particle size, and polydispersity of the NPs are varied greatly within the process parameters of the synthesis method, has been optimized. NPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…In a study as an example, bacterial surface charges of S. aureus and E. coli were reported as -13.1 mV and -2.1, respectively. It was emphasized in this study that the positive ZP formulations designed were more effective [38]. Similarly, the more effective NP-2 in our study can be explained by the high positive ZP of it.…”
Section: The Superior Time-kill Activity Of Np-2supporting
confidence: 65%
“…In a study as an example, bacterial surface charges of S. aureus and E. coli were reported as -13.1 mV and -2.1, respectively. It was emphasized in this study that the positive ZP formulations designed were more effective [38]. Similarly, the more effective NP-2 in our study can be explained by the high positive ZP of it.…”
Section: The Superior Time-kill Activity Of Np-2supporting
confidence: 65%
“…Considering its high antimicrobial effect against infections, juglone bears a promise in this respect. It has already been evidenced for herbicidal ( 9 ), antibacterial ( 10 , 11 , 12 , 13 ), antiviral ( 14 ), antifungal ( 15 , 16 ), antioxidant ( 13 ), antiparasitic ( 17 ), and anticancer ( 18 , 19 , 20 ) properties. However, its hydrophobic structure and high toxicity limit its application in biological systems ( 2 , 4 ).…”
mentioning
confidence: 99%
“…In the study by Arasoglu et al, this technique was shown to be more successful than nano-precipitation and salting out techniques used in the encapsulation of quercetin by PLGA nanoparticles. In the same study, it was found that the nanoparticles synthesized using single emulsion solvent evaporation have higher reaction yield and have a more significant antibacterial activity compared to the nanoparticles synthesized by other techniques (27). Size analysis and other characterization tests of the nanoparticles we prepared using oil-in-water single emulsion solvent evaporation technique were performed using SEM and zetasizer devices.…”
Section: Discussionmentioning
confidence: 99%
“…While quercetin and quercetin-loaded PLGA nanoparticles showed nearly similar levels of antibacterial activity on Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus, quercetin-loaded PLGA nanoparticles showed higher level of antibacterial activity on Listeria monocytogenes. The MIC value of quercetin-loaded PLGA nanoparticles on these bacteria was 100 µg/mL whereas the MIC value of quercetin alone was 200 µg/mL (27). In a similar study from 2016, Sun et al investigated the in vitro and in vivo antibacterial effects of quercetin-loaded PLGA nanoparticles on E. coli and Micrococcus tetragenus bacteria.…”
Section: Discussionmentioning
confidence: 99%